Co-hydrothermal liquefaction of microalgae and sewage sludge in subcritical water: Ash effects on bio-oil production. (August 2019) - Xu, Donghai; Wang, Yang; Lin, Guike; Guo, Shuwei; Wang, Shuzhong; Wu, Zhiqiang
Abstract: Hydrothermal liquefaction (HTL) is a promising technique of producing crude bio-oil (biocrude) from wet biomass. This work conducted the co-HTLs of microalgae (chlorella) and sewage sludge (SS) at 340 °C, 18 MPa, 0.3 MPa of initial H2 addition, 30 min of residence time under different feedstock mass ratios conditions, and explored the effects of three kinds of SS ashes on biocrude properties during microalgae HTL for the first time. Corresponding biocrude yields, elemental compositions, higher heating values, energy recoveries, boiling point distributions, and compound compositions were examined systematically. The results show that there was a certain synergistic effect on the improvement of biocrude yield other than biocrude quality in the co-HTL of microalgae and SS, especially at the 1:1 of mass ratio condition. This co-HTL could improve the actual biocrude yield by 4.7 wt% and decrease the actual solids yield by 3.6 wt% in contrast to corresponding theoretical yields. The pyrolysis-state SS ash could reduce the N and O contents, increase the C and H contents and HHV, and improve the proportion of low-boiling-point (<250 °C) compounds in the biocrude from microalgae HTL, while the oxidation-state or reduction-state SS ash was able to increase biocrude yield by approximately 3.3 wt%. Highlights: Co-hydrothermal liquefaction of microalgae and sewage sludge were explored. Effects of three types of SS ashes on biocrude yield and quality were studied. The co-HTL with 1:1 of SS/microalgae increased biocrude yield remarkably. Pyrolysis-state SS ash obviously improved biocrude quality in microalgae HTL. Oxidation- or reduction-state SS ash increased biocrude yield in microalgae HTL.